Proximate composition, minerals and anti-nutrients content of Finger Millet (Eleusine coracana) Conditioned at Different Temperatures (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This research evaluated the proximate, mineral and antinutrient properties of finger millet (Eleusine coracana) conditioned at different temperatures. The finger millet (Eleusine coracana) grains were obtained from a local farm in Jama’s local government area of Kaduna state, Nigeria and processed to flour after conditioning at 30, 60, 70 and 80 0C. The proximate, mineral and antnutrients analyses were carried out. For proximate composition, moisture ranged from 10.05 to 10.85 %, crude fat from 4.67 to 7.10 %, crude protein from 6.63 to 9.34 %, crude fiber from 2.63 to 2.84 %, ash from 4.54 to 5.88 % and carbohydrate from 66.21 to 68.19 % with the highest protein content in sample AOB (60 0C). Mineral compositions showed that calcium ranged from 351.65 to 366.17 mg/100g, magnesium from 117.52 to 143.72 mg/100g, iron from 0.99 to 1.98 mg/100g and potassium from 120.49 to 143.86 mg/100g. For anti-nutrients showed phytates content from 0.58 to 0.90 mg/100g, oxalate from 1.13 to 1.53 mg/100g, tannin ranged from 1.60 to 1.81 mg/100g and saponin from 0.33 to 0.38 mg/100g. Conditioning finger millet at high temperature lowers moisture and fat contents, increases protein, and a slight improvement in mineral concentration. These changes can enhance the overall nutritional value of finger millet, with moderate temperature between 60 0C to 70 0C conditioning offering the best balance of improved protein content and reduced anti-nutrients.